A fully integrated and high precision 350 mV amplitude regulated LVDS transmitter compensating PVT variations. (November 2018) - Lee, Seng Siong; Lee, Lini; Kung, Fabian Wai Lee; Saad, Ahmed; Tan, Gim Heng
Abstract: A low cost solution and high precision output amplitude regulation for Low-Voltage Differential Signaling (LVDS) driver targeted for TIA/EIA-644-A standard is reported. The proposed architecture has high tolerance towards internal resistors variations by adapting continuous calibration of output amplitude through a negative-feedback loop. It eliminates the requirements of high precision or expensive external resistor or post-fabrication calibration. Fabricated in 0.13-μm CMOS with a supply voltage of 3.3 V, the prototype exhibits regulated 700 mV output amplitude which is able to compensate for process, voltage and temperature (PVT) variations.